Research on Unidirectional Traveling Wire Electrochemical Discharge Micromachining of Thick Metal Materials - Rudong Zhang; Xiaocong Tang; Yaowu Zhou; Ying Li; Yongbin Zeng (Metals, 2025)
Wire electrochemical discharge machining (WECDM) integrates the effectiveness of electrical discharge machining (EDM) with the superior quality of electrochemical machining (ECM), leading to enhanced machining efficiency, excellent surface finish, and significant potential for advancement. However, previous research has mainly focused on the processing of non-metallic materials, with little research in the field of the microfabrication of thick metal materials. The wire electrochemical discharge machining process with large aspect ratios is more complex. Accordingly, a unidirectional traveling wire electrochemical discharge micromachining (UWECDMM) method using a glycol-based electrolyte was proposed. The method employs a glycol solution with low conductivity and a neutral salt, facilitating enhanced mass transfer efficiency through a unidirectional traveling wire, and enabling the realization of high-efficiency, high-precision, and recast-free processing. The phenomenon of discharge in UWECDMM was observed in real-time with a high-speed camera, while the voltage and current waveforms throughout the machining process were carefully analyzed. It was found that electrolysis and discharge alternate. Experiments were conducted to investigate the wire traveling pattern, the recast layer, and the wear of the wire electrode. It was found that due to the small energy of a single discharge, the wear of wire electrodes is minimal after multiple uses and can be reused. Under optimal parameters, a machined surface without a recast layer can be obtained. In the final stages, a standard structure was machined on plates of 10 mm thickness made of pure nickel and 304 stainless steel, using a tungsten wire measuring 30 μm in diameter. The feed rate achieved was 1 μm/s, the surface roughness (Ra) measured 0.06 μm, and the absence of a recast layer confirmed the method’s sustainability and quality traits, indicating significant potential in microfabrication.